Prevalence of methotrexate intolerance in juvenile idiopathic arthritis and possible risk factors: a tertiary center experience - Zahide Ekici Tekin; Melike Mehveş Kaplan; Merve Cansu Polat; Elif Çelikel; Vildan Güngörer; Tuba Kurt; Nilüfer Tekgöz; Müge Sezer; Cüneyt Karagöl; Serkan Coşkun; Nimet Öner; Banu Çelikel Acae (Galenos Publishing House, 2022)
Methotrexate that has a safe and inexpensive profile is a first choice of juvenile idiopathic arthritis treatment. Nevertheless, gastrointestinal symptoms are not serious but common side effects of methotrexate. Sometimes patients may have nausea by thinking methotrexate and even refuse methotrexate use. In this study, we aimed to define prevalence of methotrexate side effects in juvenile idiopathic arthritis and the possible risk factors for methotrexate intolerance. Methotrexate intolerance severity score showed severity of gastrointestinal symptoms. Eighty-seven patients accepted to join study and answered the questions. The prevalence of adverse events of methotrexate was 64.4% and the rate of gastrointestinal symptoms was 55.2%. The nausea (27.6%) was the most common gastrointestinal symptom. The median of methotrexate intolerance severity score was 14.5 (interquartile range: 10-18). However, there was no significant difference in main parameters between tolerant and intolerant groups and no risk factor was observed for methotrexate intolerance. As a conclusion, methotrexate is an important actor for juvenile idiopathic arthritis treatment as a first and safe drug and, prospective studies in larger cohorts is necessary to understand and prevent occurrence of gastrointestinal symptoms.